2011
DOI: 10.1515/humr.2011.024
|View full text |Cite
|
Sign up to set email alerts
|

The use of humor in the foreign language classroom: Funny and effective?

Abstract: The present paper deals with the role of humor in world language teaching and learning. The goal is to enable educators and researchers to address the phenomenon of humor in the world language classroom in its complexity by suggesting a multidisciplinary approach and by introducing a coding scheme for investigating the use of humor in the world language classroom. Finally, we will introduce an ongoing long-term study planned with the proposed design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
1
36
0
2
Order By: Relevance
“…When it comes to humour research in L2 context, Askildson (2005) examined the use of humour as a specific pedagogical tool, and reported that humour was perceived as an important part of the language learning process among both teachers and students. From psychological aspects, several studies (Forman 2011;Petraki & Nguyen 2016;Reddington 2015;Wagner & Urios-Aparisi 2011) have shown that teacher-led language play might lessen the language anxiety, and in turn, boost learner engagement in the learning process. Likewise, Pomerantz and Bell (2011) discussed the potential of humour as a 'safe house' for language learning.…”
Section: Humour In Language Classroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to humour research in L2 context, Askildson (2005) examined the use of humour as a specific pedagogical tool, and reported that humour was perceived as an important part of the language learning process among both teachers and students. From psychological aspects, several studies (Forman 2011;Petraki & Nguyen 2016;Reddington 2015;Wagner & Urios-Aparisi 2011) have shown that teacher-led language play might lessen the language anxiety, and in turn, boost learner engagement in the learning process. Likewise, Pomerantz and Bell (2011) discussed the potential of humour as a 'safe house' for language learning.…”
Section: Humour In Language Classroomsmentioning
confidence: 99%
“…The only studies that used a humour questionnaire were Askildson (2005) and Mantooth (2010). Further, through a careful analysis of several studies (Bell 2005;Berk 2000;Forman 2011, Wanzer & Frymier 1999Lucas 2005;Wagner & Urios-Aparisi 2011;Wanzer et al 2010; and others) on the use of humour in classrooms, the potential effects of humour were identified. Then, based on these recurring themes and the questionnaires used in previous studies, a pool of items was created to cover a wide range of aspects of classroom humour.…”
Section: Instrumentsmentioning
confidence: 99%
“…There is considerable debate within the literature around whether humour is a useful cross-cultural tool of communication (Wagner and Urios-Aparisi 2011). Holmes and Hay's (1997) New Zealand-based study found that humour was used differently between Maori and Pakeha participants, engendering scope for miscommunication and representing an ethnic boundary marker.…”
Section: Lamentioning
confidence: 99%
“…Students in S/WL classrooms often suffer high levels of anxiety “due to the discrepancy between their cognitive abilities and their linguistic skills” (Wagner & Urios‐Aparisi, , p. 399). Performance anxiety—the feeling of uneasiness, worry, nervousness, and apprehension experienced by nonnative speakers when learning or using the target language—can inhibit student performance in the target language and has often been reported as one of the most influential factors that impedes language learning (Horwitz, ).…”
Section: Review Of the Literaturementioning
confidence: 99%